New records of the grassland leafhopper genus Doratura Sahlberg (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from China - Duan, Yani; Zhang, Yalin (Zootaxa, 2012)
New records for the Old World grassland leafhopper genus Doratura Sahlberg from China are provided. Four species arerecorded with D. concors, D. homophyla and D. stylata recorded from China for the first time. A key to males is provided and their genitalia are illustrated.